Lateralized Periodic Discharges: Which patterns are interictal, ictal, or peri-ictal?. Issue 7 (July 2021) - Gelisse, Philippe; Crespel, Arielle; Genton, Pierre; Jallon, Pierre; Kaplan, Peter W.
Highlights: Specific criteria are proposed for Lateralized Periodic Discharges (LPDs) to be designated as "ictal/peri-ictal" or interictal/irritative brain injury. Identification of peri-ictal LPDs should lead to longer periods of video-EEG monitoring to detect seizure activity. LPDs-max, a subtype of LPDs-plus, is a pattern of refractory focal non-convulsive status epilepticus. Abstract: There is an ongoing debate if Lateralized Periodic Discharges (LPDs) represent an interictal pattern reflecting non-specific but irritative brain injury, or conversely, is an ictal pattern. The challenge is: how to correctly manage these patients? Between this apparent dichotomous distinction, there is a pattern lying along the interictal-ictal continuum (IIC) that we may call "peri-ictal". Peri-ictal means that LPDs are temporally associated with epileptic seizures (although not necessarily in the same recording). Their recognition should lead to careful EEG monitoring and longer periods of video-EEG to detect seizure activity (clinical and/or subclinical seizures). In order to distinguish which kind of LPDs should be considered as representing interictal/irritative brain injury versus ictal/peri-ictal LPDs, a set of criteria, with both clinical/neuroimaging and EEG, is proposed. Among them, the dichotomy LPDs-proper versus LPDs-plus should be retained. Spiky or sharp LPDs followed by associated slow after-waves or periods of flattening giving rise to a triphasic morphology should be included in the definition of LPDs-plus. We propose defining a particular subtype of LPDs-plus that we call "LPDs-max". The LPDs-max pattern corresponds to an ictal pattern, and therefore, a focal non-convulsive status epilepticus, sometimes associated with subtle motor signs and epileptic seizures. LPDs-max include periodic polyspike-wave activity and/or focal burst-suppression-like patterns. LPDs-max have a posterior predominance over the temporo-parieto-occipital regions and are refractory to antiseizure drugs. Interpretations of EEGs in critically ill patients require a global clinical approach, not limited to the EEG patterns. The clinical context and results of neuroimaging play key roles.